A Study on Excavation Characteristics of Tunnel with Upper-Soft Lower-Hard Stratum. (23rd September 2022) - Feng, Jun; Yang, Hui-juan; Zhang, Yu
Abstract : In view of the geological environment, in which the upper part is the "soft" layer of completely weathered siliceous rock and the lower part is the "hard" layer of weakly weathered limestone, the rail surface line is designed to pass through the interface between the upper "soft" layer and lower "hard" layer. First, the MIDAS/GTS software was used to comprehensively simulate the stress and deformation law of surrounded rock under three excavation methods, which are the positive benching and retaining core soil method, CRD method, and double side drift method, for selecting the appropriate excavation method. After the excavation method was determined, the rule of change in the stress and deformation of the surrounded rock with time in the actual excavation process was analyzed by field monitoring means. Finally, on the basis of the findings in the numerical analysis as well as the field monitoring, the engineering characteristics, such as the stress and deformation of the surrounded rock during the excavation of deep buried tunnels in the upper-soft lower-hard ground, were analyzed. The results revealed the following: (1) Under all three excavation methods, the tunnel deformation was small and met the requirements for tunnel deformation control. (2) Due to the different excavation support sequence, the distribution of lining bending moment of the three excavation methods was widely different. The bending moment of the lining produced by the positive benching method was far less than that of the other two methods. (3) Due to the difference in lithology, the stress of the tunnel lining in the thick upper "soft" and "hard" strata was mainly concentrated on the upper soft rock area, while the stress in the lower hard rock area was relatively small, and the lining stress value generated using the three excavation methods was relatively large. In general, the deformation and stress in the positive benching method construction were less than those in the other two methods. In addition, the positive benching method was convenient for mechanized operation, the construction progress was fast, and the cost was relatively low. Therefore, the positive benching and retaining core soil method is adoptable for this kind of tunnel. (4) The measured stress and deformation at the rail surface line exhibited a change law of first increase, and subsequently, this tended to be stable. The change in stress-time can be expressed by the Boltzmann function, and the change in deformation with time can be well expressed by exponential functions. (5) The stress value and deformation value detected in the actual excavation were greater than the results of the theoretical numerical analysis. However, the findings in the theoretical numerical analysis still have certain guiding significance for actual excavation.